Autoimmunity: Are we asking the right question? - Matzinger, Polly (Frontiers in Immunology, 2022)
For decades, the main question immunologists have asked about autoimmunity is “what causes a break in self-tolerance?”. We have not found good answers to that question, and I believe we are still so ignorant because it’s the wrong question. Rather than a break in self-tolerance, I suggest that many autoimmune diseases might instead be due to defects in normal tissue physiology.